The study on the of jets with smallinitial boundary layer thickness - Төлеуов, Ғ.; Есім, Н.Б.; Зейнеғабиден, Б.К.; Байғалиқызы, Б. (Recent Contributions to Physics, 2016)
In this paper we experimentally investigated the impact on small jetswith an initial thickness of the boundary layer. Just work shows thedistribution of velocity fluctuations and the static pressure. Highfrequency ripple affects mostly close to the boundary edge of the jetnozzle. Generalized data in the most pronounced (characteristic)frequency velocity fluctuations of the transition region in different typesof jets. In recent years greatly increased interest in studying the effect ofvarious control actions on the turbulent mixing in jets. This is due to theneed to intensify practices (or suppression) of the processes taking placein various technical devices, in particular, the mixing chambers inchemical technology, the combustion chamber flue devices, etc. One ofthe possible methods of active influence on the flow structure in the jet isto use acoustic vibrations. The advantage of this method lies in thebilateral nature of feedback. Depending superimposed frequency can becaused by either an increase in the rate of turbulent mixing and earlyattenuation of the jet or drop him an increase in range of a jet.